E-Moticon's Effective Curriculum Revolutionizes Technical Education: Kurikulum Efektif E-Moticon Merevolusi Pendidikan Teknik - Ramadhani, Mohammad Afif; Cahyaning Astuti, Cindy (Indonesian Journal of Innovation Studies, 2024)
This research focuses on developing an E-Moticon E-Module as a digital learning tool for classroom use in the field of basic computer network and telecommunications. Utilizing the ADDIE method, the study includes expert validation and student trials to assess the media's effectiveness. Results show an 84.31% approval rate from experts and an 82.14% acceptance rate from students, indicating high feasibility and positive reception. This E-Module addresses a knowledge gap in tailored technical learning resources and highlights the potential impact of digital media integration in enhancing classroom learning experiences. Further research is recommended to validate its broader applicability and effectiveness in larger-scale classroom settings. Highlight: Tailored Technical Resource: E-Moticon fills gaps in technical learning for classrooms. High Feasibility: Expert and student approval rates exceed 80%, validating effectiveness. Structured Development: ADDIE method ensures systematic and effective media creation. Keyword: E-Moticon, E-Module, Digital Learning, Classroom Integration, ADDIE Method